Does the South African GAAR criteria of the "misuse or abuse" of a provision included in Section 80A(c)(ii) of the Income Tax Act add any value? - Langenhoven, Allenda Glynn (Department of Finance and Tax, 2017)
Tax planning, where taxpayers arrange their affairs so as to minimize the resulting tax liability, has evolved over the last couple of decades as a result of the change in the way business is conducted by virtue of globalisation and the development in technology. It appears to have become more and more aggressive as taxpayers have the opportunity to access tax benefits not only through utilising loopholes in domestic legislation, but also through international tax loopholes. Revenue Authorities have to respond to this by employing mitigating anti-avoidance mechanisms. One such mechanism employed in South Africa ("SA") is the use of General anti-avoidance Rules ("GAAR") found in s80A-L of the Income Tax Act No. 58 of 1962 ("ITA"). To combat certain shortcomings in this GAAR's predecessor and to stay abreast of international trends, for the first time ever, a Statutory Purpose Element has been included in GAAR. This Statutory Purpose Element, as included in s80A(c)(ii) of the ITA, evaluates the misuse or abuse of the provisions of the ITA as a means to identify impermissible tax avoidance arrangements. Essentially, this calls for the application of the modern approach to statutory interpretation, where the purpose and context of the provisions of the ITA are first identified, before the misuse or abuse of these provisions can be proven. This study evaluates whether the inclusion of this Statutory Purpose Element in GAAR, adds any value or provides any additional powers to SARS when applying GAAR, especially in light of s39(2) included in the Bill of Rights of the Constitution, of 1996, ("Constitution"). The Constitution, the supreme law in SA, already calls for the modern approach to be applied to any statutory interpretation and the findings of this study indicate that s80A(c)(ii) appears to be completely superfluous as it does not award any additional powers to SARS, which were not already granted by the Constitution. If anything, s80A(c)(ii) broadens the scope of GAAR to such an extent, that it most likely will only cause further confusion for taxpayers wanting to engage in tax planning.